Development of a psychosocial diagnostic assessment instrument for elementary school students - Faridl Musyadad; Miftahuddin (Jurnal Konseling dan Pendidikan, 2026)
Despite the growing emphasis on adaptive and inclusive learning in basic education, diagnostic assessments used in elementary schools remain predominantly academic and cognitive in orientation, providing limited insight into students’ psychosocial readiness for learning. This gap is particularly evident in the absence of validated instruments capable of diagnosing students’ sense of safety, learning comfort, enjoyment, and learning preferences as foundational conditions for differentiated and responsive instruction. Addressing this conceptual and methodological gap, this study aims to develop and psychometrically validate a psychosocial diagnostic assessment instrument for elementary school students to support adaptive learning practices. Using a quantitative Research and Development (R&D) design, the study was conducted through stages of needs analysis, construct formulation, content validation, and field testing. The instrument was administered in seven elementary schools in Kapanewon Pengasih, Kulon Progo Regency, Indonesia, involving 7 principals, 16 teachers, and 255 fourth- and fifth-grade students. Data were analyzed using Aiken’s V to examine content validity, exploratory factor analysis (EFA) to confirm construct structure, and Cronbach’s Alpha to assess internal consistency reliability. The results indicate that the developed instrument comprises four coherent psychosocial dimensions—sense of safety, learning comfort, learning enjoyment, and learning preferences—with high content validity (V = 0.89) and excellent reliability (α = 0.87). These findings demonstrate that the instrument meets key psychometric criteria and is suitable for use as an early diagnostic tool to inform formative and differentiated learning strategies. In conclusion, this study contributes to the advancement of holistic assessment theory by extending diagnostic assessment beyond academic domains and offers a validated methodological framework for psychosocial diagnostics in primary education. Practically, the instrument provides educators with an evidence-based tool to design adaptive, inclusive, and student-centered learning aligned with contemporary curriculum demands.